Defending against the pirate evolution attack. (2nd July 2010) - Jin, Hongxia; Lotspiech, Jeffrey; Pehlivanoglu, Serdar
A trace and revoke scheme is an encryption scheme to make sure that only authorised users can access the content. When a clone device is recovered, the 'trace' component detects the pirate users that have compromised the secret keys in their devices and contributed to the clone device. In a pirate evolution attack, attackers release the compromised secret keys very slowly through a number of generations of pirate decoders that will take long time to disable them all. In this paper we will show an easy and efficient approach for the state-of-art subset difference based trace-revoke scheme to defend well against this attack. Our solution is deployed in AACS, the industry new content protection standard for high definition DVDs. We believe the pirate evolution tolerance bound should be considered carefully while designing a scheme. We formally analyse the trade off between the immunity to evolution attack and revocation efficiency.